Trash in the Streets : Amsterdam's free gay newspaper. (Amsterdam : Trash in the streets.)
Fonds Suzan Daniel (FSD)
Periodiciteit: driewekelijks
Redactie: Suite 61, Nieuwezijds Voorburgwal 353, 1012 RM Amsterdam
Vanaf 03(1995) : Out on the Streets
Engels
Periodiek